If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3n + -6n = -15 Combine like terms: 3n + -6n = -3n -3n = -15 Solving -3n = -15 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Divide each side by '-3'. n = 5 Simplifying n = 5
| 4y-13= | | 4y+38=20+8y | | 2(x+15)=x+21 | | y(49/60)=(7/2) | | x+15=x+21 | | =ln(0.5x^2) | | ((x^2)+y)dx=-xdy | | 6(2n-2)=(8n+8)+1 | | a=1/2bc2 | | (5x-14)+90+y=180 | | 3n-1=-28 | | 4a+8=2a | | 5m-1=14 | | 5L-12=38 | | (2x+13)+3x+57=180 | | -k+5=24 | | -8j-59=13 | | 5*x+57= | | 14i-5=-33 | | 14I-5=-93 | | 3(x-2)+2x=7-(x+5) | | (2c-3)(2c+4)(2c-1)=0 | | 70=(x*x+2*2) | | -12g-4=44 | | -10m+8=-8 | | (x^2+9x+4)=0 | | 6(x-5)=50-4x | | 19f+36=112 | | 5m+7m=17 | | 11e-4=-48 | | X+9y=89 | | 11e-4=44 |